2022
DOI: 10.21203/rs.3.rs-1135115/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Severely underestimated rate of wind speed decline jeopardizes China's carbon peak emission target

Abstract: The development of wind energy is indispensable in the pursuit of global carbon neutrality. Following decades of climate change, China's annual average wind speed has shown a clear decline, but the rate of this decline and its potential impacts on the need for wind power development in China have not been quantified. Here, we reveal that China's observed wind speed has declined significantly at -0.169 m/s/10 yr, 33.33 times the rate predicted by the Coupled Model Intercomparison Project (CMIP) of World Climate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Lin Boqiang et al [8] also used the LMDI model and STIRPA model to measure the factors influencing per capita carbon emissions in China and found that industrial structure, energy con-sumption structure, and energy intensity substantially impact China's carbon emis-sions, particularly industrial energy intensity. Wang Feng and Wu Lihua [9] used the LMDI method to decompose carbon emission growth from 1995 to 2007, resulting from the combined effect of 11 factors, introducing new variables such as the number of transportation modes and average annual household income. Other scholars, like Li Bo et al [10] found that efficiency and structural factors and labor force size demonstrated suppressive effects on China's agricultural carbon emissions.…”
Section: Literature Review 21 a Study Of The Factors That Contribute ...mentioning
confidence: 99%
“…Lin Boqiang et al [8] also used the LMDI model and STIRPA model to measure the factors influencing per capita carbon emissions in China and found that industrial structure, energy con-sumption structure, and energy intensity substantially impact China's carbon emis-sions, particularly industrial energy intensity. Wang Feng and Wu Lihua [9] used the LMDI method to decompose carbon emission growth from 1995 to 2007, resulting from the combined effect of 11 factors, introducing new variables such as the number of transportation modes and average annual household income. Other scholars, like Li Bo et al [10] found that efficiency and structural factors and labor force size demonstrated suppressive effects on China's agricultural carbon emissions.…”
Section: Literature Review 21 a Study Of The Factors That Contribute ...mentioning
confidence: 99%